(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study investigates the role of social media in driving marketing efficiency and business profitability within the UK automotive sector. The topic addresses a gap in current literature concerning the quantitative impact of social media on key business performance indicators. The primary objectives are to quantify the relationship between social media metrics and marketing efficiency, analyse the impact of social media activities on profitability, and identify the most influential social media platforms and metrics. The study employs a quantitative design using a descriptive and correlational approach with a multiple case study of five leading automotive companies: Tesla, Renault, Volkswagen, Mercedes-Benz, and Porsche. The methodology relies on collecting five years of secondary financial data and social media engagement data. The results reveal a complex and non-uniform relationship between social media engagement and business success. For brands like Tesla and Renault, expensive, high-engagement content on platforms like Instagram and YouTube showed a negative correlation with Marketing Efficiency Ratio (MER), suggesting a trade-off between short-term efficiency and long-term brand building. Conversely, premium brands like Mercedes-Benz and Porsche demonstrated that a well-aligned multi-platform strategy can positively impact profitability metrics like ROI and ROA. A unique finding was the significant positive influence of niche platforms like Tumblr on Porsche’s profitability, even without a direct link to sales, highlighting the value of building brand equity and community. The study concludes that the effectiveness of social media is highly contingent on the brand, platform, and specific business goals, recommending a data-driven, strategic approach rather than a one-size-fits-all model.